Practicality of Science E-Module with the Argument-Driven Inquiry Model to Improve the 21st Century Abilities Students - Susilawati; Amalia Syuzita; AA Sukarso (Postgraduate, University of Mataram, 2023)
The development of an E-module based on Argument-Driven Inquiry assisted by 3D Pageflip Professional has been carried out to improve students' 21st century abilities which include generic science abilities, critical thinking and scientific argumentation. This development aims to describe the validation of e-module teaching materials that are suitable for use in learning activities. The development model design used is 4D which consists of definition, design, development and dissemination stages. This research is limited only to the development stage. Practicality testing activities have been carried out through distributing teacher and student response questionnaires, and the implementation of learning carried out during ongoing learning activities by observers. The results show that the Argument-Driven Iberad based electronic module is in the very practical category and can be used in science learning activities in schools.